Markers of the ageing macrophage: a systematic review and meta-analysis - Moss, Charlotte E.; Phipps, Hew; Wilson, Heather L.; Kiss-Toth, Endre (Frontiers in Immunology, 2023)
Ageing research is establishing macrophages as key immune system regulators that undergo funcConal decline. Due to heterogeneity between species and Cssue populaCons, a plethora of data exist and the power of scienCfic conclusions can vary substanCally. This meta-analysis by informaCon content (MAIC) and systemaCc literature review (SLR) aims to determine overall changes in macrophage gene and protein expression, as well as funcCon, with age.PubMed was uClized to collate peer-reviewed literature relaCng to macrophage ageing. Primary studies comparing macrophages in at least two age groups were included. Data pertaining to gene or protein expression alongside method used were extracted for MAIC analysis. For SLR analysis, data included all macrophage-specific changes with age, as well as species, ontogeny and age of groups assessed.A total of 240 studies were included; 122 of which qualified for MAIC. The majority of papers focussed on changes in macrophage count/infiltraCon as a funcCon of age, followed by gene and protein expression. The MAIC found iNOS and TNF to be the most commonly invesCgated enCCes, with 328 genes and 175 proteins showing consistent dysregulaCon with age across the literature. Overall findings indicate that cytokine secreCon and phagocytosis are reduced and reacCve oxygen species producCon is increased in the ageing macrophage.CollecCvely, our analysis idenCfies criCcal regulators in macrophage ageing that are consistently dysregulated, highlighCng a plethora of targets for further invesCgaCon. Consistent funcConal changes with age found here can be used to confirm an ageing macrophage phenotype in specific studies and experimental models.